1993
DOI: 10.1111/j.1365-3016.1993.tb00415.x
|View full text |Cite
|
Sign up to set email alerts
|

The Dutch famine birth cohort study: design, validation of exposure, and selected characteristics of subjects after 43 years follow‐up

Abstract: A historical birth cohort study of 1116 women born between August 1 1944 and April 15 1946 in the Wilhelmina Gasthuis hospital in Amsterdam, the Netherlands, was set up to study the short- and long-term effects of a limited period of extreme nutritional deprivation in the winter of 1944-1945 in the Western Netherlands. The degree of food deprivation is evidenced by a dramatic decline in third trimester pregnancy weight gain and infant birthweight. All women were traced and 84% (683/813) of survivors presently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
0
3

Year Published

1997
1997
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(62 citation statements)
references
References 4 publications
1
58
0
3
Order By: Relevance
“…This raises a possibility that dysregulation of DNA methylation of the Ptger1 gene in females may underlie the mechanism of preterm birth in maternal undernutrition. It has been clinically and experimentally shown that preterm birth rate increases in the cohort conceived during famine and animals fertilized under CR (8,20,35,36,51,54). Ptger1 mediates the effect of prostaglandin E2 (PGE2), an uterotonic agent that is clinically used for prevention of postpartum hemorrhage as well as induction of abortion.…”
Section: Discussionmentioning
confidence: 99%
“…This raises a possibility that dysregulation of DNA methylation of the Ptger1 gene in females may underlie the mechanism of preterm birth in maternal undernutrition. It has been clinically and experimentally shown that preterm birth rate increases in the cohort conceived during famine and animals fertilized under CR (8,20,35,36,51,54). Ptger1 mediates the effect of prostaglandin E2 (PGE2), an uterotonic agent that is clinically used for prevention of postpartum hemorrhage as well as induction of abortion.…”
Section: Discussionmentioning
confidence: 99%
“…Details on the recruitment process have been published elsewhere (16). The obstetric records of all 1,116 females born between August 1, 1944, andApril 15, 1946, at the Department of Obstetrics and Gynecology, Wilhelmina Gasthuis Hospital (Amsterdam, The Netherlands), were identified.…”
Section: Study Populationmentioning
confidence: 99%
“…Even extreme exposures such as famine (15) and maternal smoking during pregnancy (16) result in birth weight changes of only a few hundred grams. However, it is likely that birth weight is a marker for other exposures (e.g., fetal nutrition, genetic factors, epigenetic factors) (17) and thus one would expect weak or modest associations of birth weight with later health related outcomes, but associations with the "real" developmental exposures should be stronger.…”
mentioning
confidence: 99%